Perancangan Ulang Tata Letak untuk Pengoptimalisasian Ruang pada Bebeke Om Aris Dramaga Kota Bogor - M. Egitia Zaini; Jilan Rifa Fauziah; Angelica Meilani Rika Dwi Kusuma; Nova Pebi Rachmawati br. Sembiring; Putra Fajar Setiawan; Wawan Oktariza; Tina Nur Ainun (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the era of increasingly rapid globalization, the industrial world is faced with inevitable dynamics. One important aspect in industry is optimal layout planning. The right layout determines the effective placement of production facilities, thereby smoothing the production process and increasing productivity. The current layout of production facilities at Bebeke Om Aris Dramaga is not optimal, causing production inefficiencies and increased costs. This research aims to redesign the layout of facilities at Bebeke Om Aris Dramaga. This research examines the design of alternative layouts at Bebeke Om Aris Dramaga with the aim of increasing productivity. The methods used are Activity Relationship Chart (ARC) and Total Closeness Rating (TCR). Production location calculations are carried out periodically to obtain accurate information. The research results show that the proposed layout has shorter distances between facilities. Apart from that, the resulting service time is more optimal. This change in store layout shows that the new layout is more effective and efficient than the old layout. This is proven by research results which show that the new layout design can reduce the time spent by employees in the production process and service to customers and the distance between facilities and increase the efficiency of employee movement.